Incidence and clinical relevance of persistent iatrogenic atrial septal defect after percutaneous mitral valve repair - Mhd Nawar Alachkar (Nature Portfolio, 2021)
Abstract Percutaneous mitral valve repair (PMVR) requires transseptal puncture and results in iatrogenic atrial septal defect (iASD). The impact of persistent iASD was previously investigated. However, data were diverse and inconclusive. 53 patients who underwent MITRACLIP were retrospectively included. Based on the presence of iASD in transesophageal echocardiography (TEE) after 6 months, patients were divided in two groups (iASD group vs. non-iASD group). Impact of iASD on outcome at 6 months and at two years was evaluated. Persistent iASD was detected in 62% of patients. Independent predictors for persistent iASD were female gender and reduced left ventricular ejection fraction. At 6-month follow-up, there was no difference in reduction of NYHA class (ΔNYHA = 1.3 ± 1 in iASD group vs. 0.9 ± 1 in non-iASD group, p = 0.171). There was a significant difference in right ventricular end diastolic diameter (RVEDd) (42 ± 8 mm in iASD-group vs. 39 ± 4 mm in non-iASD group, p = 0.047). However, right ventricular systolic function (TAPSE) (14 ± 7 mm in iASD group vs. 16 ± 8 mm in non-iASD group, p = 0.176) and right ventricular systolic pressure (RVSP) (40 ± 12 mmHg in iASD group vs. 35 ± 10 mmHg in non-iASD group, p = 0.136) were still comparable between both groups. At 2 years follow-up, there was no significant difference regarding rate of rehospitalization (24% vs 15%, p = 0.425) or mortality (12% vs 10%, p = 0.941) between both groups. Incidence of persistent iASD after MITRACLIP is markedly high. Despite the increase in right ventricular diameter in patients with persistent iASD, these patients were not clinically compromised compared to patients without persistent iASD.